Association between the T6459C point mutation of the mitochondrial MT‐CO1 gene and susceptibility to sepsis among Chinese Han people. Issue 11 (11th September 2018) - Shen, Xiaodong; Han, Guoxin; Li, Shuoshuo; Song, Yang; Shen, Hong; Zhai, Yongzhi; Wang, Yingchan; Zhang, Fei; Dong, Ning; Li, Tanshi; Yao, Yongming; Zhu, Haiyan
Abstract: To search for an association between sepsis and mitochondrial genetic basis, we began our study. In this study, a proband harbouring mitochondrial T6459C mutation with sepsis and his Chinese Han pedigree including 7 members of 3 generations were enrolled. General information, blood parameters and mitochondrial full sequence scanning of all members were performed, and cellular functions, including cellular reactive oxygen species (ROS) levels, mitochondrial membrane potential (MMP), degrees of cell apoptosis and adenosine triphosphate (ATP) concentrations, were measured in members with and without the T6459C mutation. Through mitochondrial full sequence scanning and analysis of all members we found, the maternal members (I‐1, II‐1, II‐2 and II‐4) in this Chinese Han pedigree all had the mitochondrial T6459C mutation and were used as the mutation group. The non‐maternal members (II‐3, III‐1 and III‐2) did not have this mutation and were used as the non‐mutation group. The differences in all indicators, including the blood routine, blood biochemistry and coagulation function tests, between members in these two groups were not significant. Under the non‐stimulation condition, the mutation group had higher ROS levels (4210.42 ± 1043.35 vs 3387.78 ± 489.66, P = .028) and apoptosis ratios ( P = .004) and lower ATP concentrations ( P = .049) and MMP levels ( P = .047) than the non‐mutation group. After 6 hours of simulated LPS stimulation, the mutation group had significantly increased ROS levels (5759.25 ± 2297.90 vs 3862.00 ± 1519.77, P = .045) compared with the non‐mutation group, whereas the mutation group continued to demonstrate higher ROS levels ( P = .045) and apoptosis ratios ( P = .003) and lower MMP levels ( P = .005) and ATP concentrations ( P = .010). We speculated that the mtDNA T6459C mutation might be the basis for the genetic susceptibility to sepsis.